Recombinant Human Thrombopoietin Accelerates the Recovery of Platelet in Patients With Lower-Risk Myelodysplastic Syndrome: A Proof-of-Concept Study - Yang, Yuan; Tang, Zengwei; Ji, Jiang; Yang, Chen; Chen, Miao; Han, Bing (Frontiers in Oncology, 2021)
Aim The effect of recombinant human thrombopoietin (rhTPO) is largely unknown in lower-risk myelodysplastic syndrome (LR-MDS). This study aimed at investigating the safety and efficacy of rhTPO in patients with LR-MDS. Methods LR-MDS patients receiving stanozolol (2 mg, t.i.d.) and supportive care alone (non-rhTPO) or additional rhTPO were enrolled in this study prospectively. rhTPO was given at 15,000 U (q.d.) for 7 days/month for at least 3 months. Patients stopped rhTPO if the platelet count was higher than 50 × 109/L or had no effects after 3 months of treatment. The overall response (OR), complete response (CR), platelet response, side effects, clone evolution, and clinical outcome were evaluated. Result Thirty-five patients were enrolled: 20 (57.1%) patients in the rhTPO group and 15 (42.9%) patients in the non-rhTPO group. The demographic and baseline characteristics were balanced between the two groups. Platelet response was higher at 1 and 2 months as compared with that in the non-rhTPO group (p = 0.006 and p = 0.001, respectively). Meanwhile, the rhTPO group had a shorter time to achieve a platelet transfusion-free state compared with the non-rhTPO group (p = 0.034). Hematologic response was higher at 1 and 2 months compared with that in the non-rhTPO group (p = 0.006 and p = 0.001, respectively). There was no significant difference in the overall response or complete response at 1, 2, 3, 6, and 12 months between the two groups. One patient in the rhTPO group evolved into higher-risk MDS at 9 months. No significant difference in disease progression, infection, gastrointestinal disorders, or drug-related liver/renal injuries was found between the two groups (p > 0.05). Conclusion Adding short-term rhTPO can accelerate the early platelet response and decrease platelet transfusion, with no obvious side effects. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT04324060?cond=NCT04324060&draw=2, identifier NCT04324060